Components of spraying type white thermal control coating suitable for magnesium-lithium alloy and preparation method of spraying type white thermal control coating
Through the composition and preparation method of the spray-type white thermal control coating, it is directly applied on the surface of magnesium-lithium alloy, which solves the problems of insufficient adhesion of magnesium-lithium alloy surface coating and difficulty in achieving heat balance in the existing technology, and achieves high adhesion. Focus on thermal control effect with low absorption and high emission.
Patent Information
- Application Number
- CN202411490907.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-21
AI Technical Summary
The existing white thermal control coating is not suitable for magnesium lithium alloys, which leads to insufficient adhesion and may bring the risk of product deformation, and it is difficult to achieve low absorption and high emission heat balance.
The components of the spray-type white thermal control coating are used, including methyl silicone resin as the adhesive, zinc oxide, titanium oxide, etc. as fillers, polymethylsilazane as the curing agent, and triethylenetetramine, etc. as the catalyst. Butyl acetate and the like are used as solvents, prepared through steps such as mechanical stirring and filtration, and then directly sprayed on the surface of the magnesium-lithium alloy substrate and solidified.
A thermal control coating with high adhesion, low solar absorption ratio and high hemispheric emissivity on the surface of magnesium-lithium alloy is achieved to ensure that the surface of magnesium-lithium alloy is within the desired temperature range, solving the problems of insufficient adhesion and heat balance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal control coatings for spacecraft, and relates to a component and a preparation method of a spray-type white thermal control coating suitable for magnesium-lithium alloys. Background Art
[0002] With the advancement of aerospace technology, satellites, spacecraft and other spacecraft are developing towards large-scale, high-precision and multi-functional aspects, which leads to the continuous increase of the payload of spacecraft, thus putting forward higher requirements for the lightweight structure of spacecraft. Magnesium-lithium alloy is the lightest metal structural material at present. It not only has the characteristics of magnesium alloy, but also has the characteristics of low density and strong resistance to high-energy particle penetration. It is an ideal material for spacecraft to achieve structural weight reduction and has good application prospects in the field of spacecraft.
[0003] Thermal control coating is an important part of the thermal control system of spacecraft. It adjusts the solar absorption ratio (α S ) and hemispherical emissivity (ε H ) is used to control the thermal balance of the spacecraft to ensure that the spacecraft itself and the spacecraft's own payload are always within normal operating temperatures. In order to ensure the thermal stability of spacecraft payload products in the space environment, it is necessary to increase the space radiation heat dissipation capacity of the surface of the payload product structural parts. Therefore, it is necessary to apply a thermal control coating on the surface of the magnesium-lithium alloy structural parts. The existing white thermal control coating is suitable for substrates such as aluminum alloys, titanium alloys, and composite materials. Before applying the thermal control coating, it will be sandblasted or polished, but the magnesium-lithium alloy has extremely high chemical activity. After surface polishing or sandblasting, the adhesion still cannot meet the use requirements and will bring the risk of product deformation. Summary of the invention
[0004] The invention provides a component and a preparation method of a spray-coated white thermal control coating suitable for magnesium-lithium alloys.
[0005] A component of a spray-type white thermal control coating suitable for magnesium-lithium alloys, characterized in that the components calculated by weight ratio are:
[0006] Adhesive is 150-360 parts,
[0007] The filler is 200 to 400 parts,
[0008] The curing agent is 25 to 72 parts,
[0009] The catalyst is 0.03 to 0.72 parts,
[0010] The solvent is 200 to 450 parts, and each component is mixed and prepared;
[0011] Wherein, the binder is a methyl silicone resin; wherein the solid content of the methyl silicone resin is ≥40%, preferably 45% to 55%;
[0012] The filler is one of zinc oxide, titanium dioxide, zirconium dioxide, silicon dioxide, and aluminum oxide, or a mixture of several of them in any ratio;
[0013] The curing agent is polymethylsilazane;
[0014] The catalyst is one or a mixture of triethylenetetramine, diisopropanolamine, N,N-dimethylaniline, and diisopropylbenzene peroxide;
[0015] The solvent is one of butyl acetate, xylene and propylene glycol methyl ether acetate or a mixture of several of them.
[0016] The components can also be calculated by weight ratio:
[0017] The adhesive is 200-300 parts of methyl silicone resin;
[0018] The filler is 240-380 parts, one of zinc oxide, titanium dioxide, zirconium dioxide, silicon dioxide, aluminum oxide or a mixture of several of them in any ratio;
[0019] The curing agent is 34 to 60 parts of polymethylsilazane;
[0020] The catalyst is 0.04-0.20 parts, one or a mixture of triethylenetetramine, diisopropanolamine, N,N-dimethylaniline, diisopropylbenzene peroxide,
[0021] The solvent is 300-400 parts, which is one or a mixture of butyl acetate, xylene, and propylene glycol methyl ether acetate.
[0022] The components can also be calculated by weight ratio:
[0023] The adhesive is 200 parts of methyl silicone resin.
[0024] The filler is 130 to 155 parts of zinc oxide, 30 to 35 parts of titanium dioxide, and 65 to 80 parts of zirconium dioxide.
[0025] The curing agent is 34 to 40 parts of polymethylsilazane,
[0026] The catalyst is 0.04-0.40 parts of diisopropanolamine,
[0027] The solvent is composed of 300 to 350 parts of propylene glycol methyl ether acetate.
[0028] The components can also be calculated by weight ratio:
[0029] The adhesive is 250 parts of methyl silicone resin.
[0030] The filler is 160 to 180 parts of zinc oxide, 40 to 45 parts of zirconium dioxide, 60 to 80 parts of silicon dioxide, and 80 to 100 parts of aluminum oxide.
[0031] The curing agent is 42 to 50 parts of polymethylsilazane,
[0032] The catalyst is 0.08 to 0.11 parts of N,N-dimethylaniline,
[0033] The solvent is composed of 300 to 350 parts of propylene glycol methyl ether acetate.
[0034] The components can also be calculated by weight ratio:
[0035] The adhesive is 250 parts of methyl silicone resin.
[0036] The filler is 160 to 180 parts of zinc oxide, 20 to 20 parts of zirconium dioxide, and 40 to 47 parts of silicon dioxide.
[0037] The curing agent is 42 to 50 parts of polymethylsilazane,
[0038] The catalyst is 0.08 to 0.11 parts of N,N-dimethylaniline,
[0039] The solvent consists of 250-300 parts of xylene and 50-80 parts of propylene glycol methyl ether acetate.
[0040] The components can also be calculated by weight ratio:
[0041] The adhesive is 300 parts of methyl silicone resin.
[0042] The filler is 250 to 280 parts of zinc oxide and 80 to 100 parts of zirconium dioxide.
[0043] The curing agent is 50-60 parts of polymethylsilazane,
[0044] The catalyst is 0.06-0.20 parts of dicumyl peroxide,
[0045] The solvent consists of 100 to 120 parts of butyl acetate and 150 to 200 parts of xylene.
[0046] A method for preparing a spray-type white thermal control coating comprises the following steps:
[0047] Step 1, weigh the adhesive, filler and solvent according to the weight ratio, add the adhesive and filler into the solvent, and disperse them evenly, use mechanical stirring during dispersion, the size of the glass beads used in the dispersion process is 2 to 3 mm, the amount of glass beads is 1 to 1.3 times the total weight of the filler and the adhesive, the stirring speed is 1200 to 2000 rpm / min, and the dispersion time is 30 to 60 min;
[0048] Step 2: Filter and sift out the glass beads;
[0049] Step 3: Add curing agent and catalyst, and stir evenly for no less than 3 minutes to obtain paint;
[0050] Step 4: Filter the paint with a 120-200 mesh filter;
[0051] Step 5: spraying in an environment of 10°C to 25°C and relative humidity of 20% to 60%, adjusting the spraying pressure to 0.3MPa to 0.5MPa, the spraying distance to 150mm to 250mm, the single spraying to 10 to 25μm, the total spraying thickness to 150 to 200μm, and the surface drying time to 10min to 30min;
[0052] Step 6: When the curing method is heat curing, the curing temperature is 60-120°C and the curing time is 2-10 hours. When the curing method is room temperature curing, the curing time is 24-72 hours, preferably 48-72 hours.
[0053] The thermal control coating has a thickness of 150 to 200 μm, a solar absorption ratio of 0.13 to 0.19, a hemispherical emissivity of 0.87 to 0.91, an adhesion of 0 to 1, and a substrate of aluminum alloy, magnesium alloy, magnesium-lithium alloy, titanium alloy, carbon fiber composite material or glass fiber composite material.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] 1. The thickness of the spray-coated white thermal control coating prepared by the method of the present invention is between 150 and 200 μm, the solar absorption ratio is 0.13 to 0.19, the hemispherical emissivity is 0.87 to 0.91, and the adhesion is 0 to 1 level. The comprehensive performance of the present invention is excellent.
[0056] 2. The present invention solves the problem that the existing white thermal control coating is not suitable for magnesium-lithium alloys. It is directly applied to the surface of the magnesium-lithium alloy substrate of the spacecraft by spraying, and has an adhesion of 0 to 1 with the magnesium-lithium alloy, achieving low absorption and high emission performance, so that the surface of the magnesium-lithium alloy is within the desired temperature range.
[0057] 3. The present invention is applicable to aluminum alloys, magnesium alloys, magnesium-lithium alloys, titanium alloys, carbon fiber composites or glass fiber composites. The present invention has the advantages of easy production, simple construction process, short spraying cycle, high production efficiency, and is suitable for large-scale promotion and use. DETAILED DESCRIPTION
[0058] The thermal control coating of the invention is prepared by mixing 150-360 parts of an adhesive, 200-400 parts of a filler, 25-72 parts of a curing agent, 0.03-0.72 parts of a catalyst and 200-450 parts of a solvent in a weight ratio.
[0059] Preferably, calculated by weight ratio: the adhesive is 200-300 parts, the filler is 240-380 parts, the curing agent is 34-60 parts, the catalyst is 0.04-0.20 parts and the solvent is 300-400 parts.
[0060] The preparation method of the present invention is carried out according to the following steps:
[0061] Step 1, weigh the adhesive, filler and solvent according to the weight ratio, add the adhesive and filler into the solvent, and disperse them evenly, use mechanical stirring during dispersion, the size of the glass beads used in the dispersion process is 2 to 3 mm, the amount of glass beads is 1 to 1.3 times the total weight of the filler and the adhesive, the stirring speed is 1200 to 2000 rpm / min, and the dispersion time is 30 to 60 min;
[0062] Step 2: Filter and sift out the glass beads;
[0063] Step 3: Add curing agent and catalyst, and stir evenly for no less than 3 minutes to obtain paint;
[0064] Step 4: Filter the paint with a 120-200 mesh filter;
[0065] Step 5: spraying in an environment of 10°C to 25°C and relative humidity of 20% to 60%, adjusting the spraying pressure to 0.3MPa to 0.5MPa, the spraying distance to 150mm to 250mm, the single spraying to 10 to 25μm, the total spraying thickness to 150 to 200μm, and the surface drying time to 10min to 30min;
[0066] Step 6: When the curing method is heat curing, the curing temperature is 60-120°C and the curing time is 2-10 hours. When the curing method is room temperature curing, the curing time is 24-72 hours, preferably 48-72 hours.
[0067] It is further defined that the binder methyl silicone resin has a solid content of ≥40%, preferably 45% to 55%;
[0068] It is further defined that the filler is one of zinc oxide, titanium dioxide, zirconium dioxide, silicon dioxide, and aluminum oxide, or a mixture of several of them in any ratio;
[0069] It is further defined that the curing agent is polymethylsilazane;
[0070] It is further defined that the catalyst is one or more of triethylenetetramine, diisopropanolamine, N,N-dimethylaniline, and diisopropylbenzene peroxide.
[0071] It is further defined that the solvent is one or more of butyl acetate, xylene, and propylene glycol methyl ether acetate.
[0072] It is further defined that the substrate of the present invention is an aluminum alloy, a magnesium alloy, a magnesium-lithium alloy, a titanium alloy, a carbon fiber composite material (epoxy / carbon fiber, phenolic / carbon fiber, bismaleimide / carbon fiber) and a glass fiber composite material (epoxy / glass fiber, bismaleimide / glass fiber), wherein the carbon fiber composite material and the glass fiber composite material must be polished with 80-200 mesh sandpaper before the thermal control coating is applied, and the aluminum alloy, magnesium alloy, and titanium alloy are sandblasted with 0.1-0.3 MPa pressure and 40-60 mesh corundum before the thermal control coating is applied, or polished with 80-200 mesh sandpaper, and the magnesium alloy and magnesium-lithium alloy subjected to chemical oxidation treatment do not need to be polished or sandblasted;
[0073] The thermal control coating of the present invention has a solar absorption ratio of 0.13 to 0.19, a hemispherical emissivity of 0.87 to 0.91, and an adhesion of 0 to 1 levels.
[0074] The technical solution of the present invention is not limited to the specific implementations listed below, but also includes any combination of the specific implementations. The following examples are used to verify the beneficial effects of the present invention:
[0075] Embodiment 1:
[0076] The white thermal control coating provided in this embodiment is prepared from 200 parts of methyl silicone resin, 140 parts of zinc oxide, 30 parts of titanium dioxide, 70 parts of zirconium dioxide, 34 parts of polymethylsilazane, 0.40 parts of diisopropanolamine, 100 parts of butyl acetate and 300 parts of propylene glycol methyl ether acetate by weight.
[0077] The magnesium-lithium alloy after chemical oxidation treatment is used as the substrate, and the molding process method includes the following steps:
[0078] Step 1: weigh all raw materials according to the weight ratio, first add methyl silicone resin and filler into the solvent, and disperse them by mechanical stirring. The size of the glass beads used in the dispersion process is 2 to 3 mm, and the amount of glass beads is 1 to 1.3 times the total weight of the filler and the adhesive. The stirring speed is 1800 rpm / min, and the dispersion time is 60 min.
[0079] Step 2: Filter and sift out the glass beads;
[0080] Step 3: Add polymethylsilazane and a catalyst, and stir evenly for 3 minutes to obtain a paint;
[0081] Step 4: Filter the paint with a 200-mesh filter;
[0082] Step 5: Clean the surface of the magnesium-lithium alloy after chemical oxidation treatment with acetone and leave it in the air for more than 10 minutes;
[0083] Step 6: Spray in an environment of 10℃~25℃, relative humidity of 20%~60%, adjust the spraying pressure to 0.4MPa, spraying distance to 180~230mm, single spraying to 10~25μm, total spraying thickness to 150~200μm, surface drying time to 10~20min, and cure at room temperature for 48h.
[0084] The solar absorption ratio of the white thermal control coating obtained in Example 1 is 0.13, the hemispherical emissivity is 0.91, and the adhesion to the magnesium-lithium alloy is level 1.
[0085] Embodiment 2:
[0086] The white thermal control coating provided in this embodiment is prepared from 200 parts of methyl silicone resin, 140 parts of zinc oxide, 30 parts of titanium dioxide, 70 parts of zirconium dioxide, 40 parts of polymethylsilazane, 0.04 parts of triethylenetetramine and 350 parts of propylene glycol methyl ether acetate by weight.
[0087] The magnesium-lithium alloy after chemical oxidation treatment is used as the substrate. The molding process method is different from that of Example 1 in that the spraying pressure is adjusted to 0.4 MPa, the spraying distance is 180-230 mm, the single spraying is 10-25 μm, the total spraying thickness is 150-200 μm, the surface drying time is 15-30 min, and the curing is performed at 60° C. for 10 h.
[0088] The solar absorption ratio of the white thermal control coating obtained in Example 2 is 0.13, the hemispherical emissivity is 0.91, and the adhesion to the magnesium-lithium alloy is level 1.
[0089] Embodiment three:
[0090] The white thermal control coating provided in this embodiment is prepared from 250 parts of methyl silicone resin, 176 parts of zinc oxide, 22 parts of zirconium dioxide, 44 parts of silicon dioxide, 45 parts of polymethylsilazane, 0.10 parts of N,N-dimethylaniline, 300 parts of xylene and 50 parts of propylene glycol methyl ether acetate by weight.
[0091] The magnesium-lithium alloy after chemical oxidation treatment is used as the substrate. The molding process method is different from that of Example 1 in that the spraying pressure is adjusted to 0.5 MPa, the spraying distance is 200-250 mm, the single spraying is 10-25 μm, the total spraying thickness is 150-200 μm, the surface drying time is 10-20 min, and the room temperature curing is 24 h.
[0092] The solar absorption ratio of the white thermal control coating obtained in Example 3 is 0.16, the hemispherical emissivity is 0.89, and the adhesion to the magnesium-lithium alloy is level 0.
[0093] Embodiment 4:
[0094] The white thermal control coating provided in this embodiment is prepared from 250 parts of methyl silicone resin, 176 parts of zinc oxide, 44 parts of zirconium dioxide, 68 parts of silicon dioxide, 88 parts of aluminum oxide, 42 parts of polymethylsilazane, 0.10 parts of N,N-dimethylaniline and 300 parts of propylene glycol methyl ether acetate by weight.
[0095] The magnesium-lithium alloy after chemical oxidation treatment is used as the substrate. The molding process method is different from that of Example 1 in that the spraying pressure is adjusted to 0.3 MPa, the spraying distance is 150-200 mm, the single spraying is 10-25 μm, the total spraying thickness is 150-200 μm, the surface drying time is 15-30 min, and the curing is performed at 80° C. for 8 h.
[0096] The solar absorption ratio of the white thermal control coating obtained in Example 4 is 0.15, the hemispherical emissivity is 0.90, and the adhesion to the magnesium-lithium alloy is level 1.
[0097] Embodiment five:
[0098] The white thermal control coating provided in this embodiment is prepared from 300 parts of methyl silicone resin, 140 parts of zinc oxide, 30 parts of titanium dioxide, 70 parts of zirconium dioxide, 50 parts of polymethylsilazane, 0.10 parts of dicumyl peroxide and 300 parts of xylene by weight.
[0099] The magnesium-lithium alloy after chemical oxidation treatment is used as the substrate. The molding process method is different from that of Example 1 in that the spraying pressure is adjusted to 0.4 MPa, the spraying distance is 180-230 mm, the single spraying is 10-25 μm, the total spraying thickness is 150-200 μm, the surface drying time is 15-30 min, and the curing is performed at 120° C. for 2 h.
[0100] The solar absorption ratio of the white thermal control coating obtained in Example 5 is 0.17, the hemispherical emissivity is 0.89, and the adhesion to the magnesium-lithium alloy is level 0.
[0101] Embodiment six:
[0102] The white thermal control coating provided in this embodiment is prepared from 300 parts of methyl silicone resin, 270 parts of zinc oxide, 90 parts of zirconium dioxide, 50 parts of polymethylsilazane, 0.20 parts of dicumyl peroxide, 120 parts of butyl acetate and 200 parts of xylene by weight.
[0103] The magnesium-lithium alloy after chemical oxidation treatment is used as the substrate. The molding process method is different from that of Example 1 in that the spraying pressure is adjusted to 0.3 MPa, the spraying distance is 150-200 mm, the single spraying is 10-25 μm, the total spraying thickness is 150-200 μm, the surface drying time is 10-20 min, and the room temperature curing is 72 h.
[0104] The solar absorption ratio of the white thermal control coating obtained in Example 6 is 0.18, the hemispherical emissivity is 0.89, and the adhesion to the magnesium-lithium alloy is level 1.
[0105] The components and preparation method of a spray-type white thermal control coating suitable for magnesium-lithium alloy provided by the present invention have many advantages for technical personnel in the same industry today.
[0106] The above describes the main principles and features of the present invention, but does not limit the present invention in any form. Although the present invention is shown as above with preferred examples, it is not intended to limit the inventors and technicians familiar with the profession. Without departing from the technical scope of the present invention, the technical contents disclosed above can be used to make slight changes or modifications to equivalent embodiments of equivalent changes. These modifications, equivalent changes and modifications are all within the scope of the technical solution of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents. The present invention provides a method for preparing a spray-type white thermal control coating suitable for magnesium-lithium alloys. The method is directly implemented on the surface of a magnesium-lithium alloy substrate of a spacecraft by spraying, so as to achieve low absorption and high emission performance, so that it is within the desired temperature range. The purpose of the present invention is to solve the problem that the existing white thermal control coating is not suitable for magnesium-lithium alloys. The composition of the thermal control coating of the present invention comprises an adhesive, a filler, a curing agent, a catalyst and a solvent. The solar absorption ratio of the thermal control coating of the present invention is 0.13-0.19, the hemispherical emissivity is 0.87-0.91, and the adhesion is 0-1 level. The thermal control coating of the present invention is suitable for aluminum alloys, magnesium alloys, magnesium-lithium alloys, titanium alloys, carbon fiber composites (epoxy / carbon fiber, phenolic / carbon fiber, bismaleimide / carbon fiber) and glass fiber composites (epoxy / glass fiber, bismaleimide / glass fiber).
Claims
1. A component of a spray-type white thermal control coating suitable for magnesium-lithium alloys, characterized in that: Components calculated by weight: Adhesive is 150-360 parts, The filler is 200 to 400 parts, The curing agent is 25 to 72 parts, The catalyst is 0.03 to 0.72 parts, The solvent is 200 to 450 parts, and each component is mixed and prepared; Wherein, the binder is a methyl silicone resin; wherein the solid content of the methyl silicone resin is ≥40%, preferably 45% to 55%; The filler is one of zinc oxide, titanium dioxide, zirconium dioxide, silicon dioxide and aluminum oxide, or a mixture of several of them in any ratio; The curing agent is polymethylsilazane; The catalyst is one or a mixture of triethylenetetramine, diisopropanolamine, N,N-dimethylaniline, and diisopropylbenzene peroxide; The solvent is one of butyl acetate, xylene and propylene glycol methyl ether acetate or a mixture of several of them.
2. The components of the spray-coated white thermal control coating suitable for magnesium-lithium alloy according to claim 1, calculated by weight ratio: The adhesive is 200-300 parts of methyl silicone resin; The filler is 240-380 parts, one of zinc oxide, titanium dioxide, zirconium dioxide, silicon dioxide, aluminum oxide or a mixture of several of them in any ratio; The curing agent is 34 to 60 parts of polymethylsilazane; The catalyst is 0.04-0.20 parts, one or a mixture of triethylenetetramine, diisopropanolamine, N,N-dimethylaniline, diisopropylbenzene peroxide, The solvent is 300-400 parts, which is one or a mixture of butyl acetate, xylene, and propylene glycol methyl ether acetate.
3. The components of the spray-coated white thermal control coating suitable for magnesium-lithium alloy according to claim 1, the components calculated by weight ratio are: The adhesive is 200 parts of methyl silicone resin. The filler is 130 to 155 parts of zinc oxide, 30 to 35 parts of titanium dioxide, and 65 to 80 parts of zirconium dioxide. The curing agent is 34 to 40 parts of polymethylsilazane, The catalyst is 0.04-0.40 parts of diisopropanolamine, The solvent is composed of 300 to 350 parts of propylene glycol methyl ether acetate.
4. The components of the spray-coated white thermal control coating suitable for magnesium-lithium alloy according to claim 1, wherein the components calculated by weight ratio are: The adhesive is 250 parts of methyl silicone resin. The filler is 160 to 180 parts of zinc oxide, 40 to 45 parts of zirconium dioxide, 60 to 80 parts of silicon dioxide, and 80 to 100 parts of aluminum oxide. The curing agent is 42 to 50 parts of polymethylsilazane, The catalyst is 0.08 to 0.11 parts of N,N-dimethylaniline, The solvent is composed of 300 to 350 parts of propylene glycol methyl ether acetate.
5. The components of the spray-coated white thermal control coating suitable for magnesium-lithium alloy according to claim 1, wherein the components calculated by weight ratio are: The adhesive is 250 parts of methyl silicone resin. The filler is 160 to 180 parts of zinc oxide, 20 to 20 parts of zirconium dioxide, and 40 to 47 parts of silicon dioxide. The curing agent is 42 to 50 parts of polymethylsilazane, The catalyst is 0.08 to 0.11 parts of N,N-dimethylaniline, The solvent consists of 250-300 parts of xylene and 50-80 parts of propylene glycol methyl ether acetate.
6. The components of the spray-coated white thermal control coating suitable for magnesium-lithium alloy according to claim 1, wherein the components calculated by weight ratio are: The adhesive is 300 parts of methyl silicone resin. The filler is 250 to 280 parts of zinc oxide and 80 to 100 parts of zirconium dioxide. The curing agent is 50-60 parts of polymethylsilazane, The catalyst is 0.06-0.20 parts of dicumyl peroxide, The solvent consists of 100 to 120 parts of butyl acetate and 150 to 200 parts of xylene.
7. A method for preparing a spray-coated white thermal control coating suitable for magnesium-lithium alloys, using the components of the spray-coated white thermal control coating according to claims 1-6, characterized in that: The following steps are involved: Step 1, weigh the adhesive, filler and solvent according to the weight ratio, add the adhesive and filler into the solvent, and disperse them evenly, use mechanical stirring during dispersion, the size of the glass beads used in the dispersion process is 2 to 3 mm, the amount of glass beads is 1 to 1.3 times the total weight of the filler and the adhesive, the stirring speed is 1200 to 2000 rpm / min, and the dispersion time is 30 to 60 min; Step 2: Filter and sift out the glass beads; Step 3: Add curing agent and catalyst, and stir evenly for at least 3 minutes to obtain paint; Step 4: Filter the paint with a 120-200 mesh filter; Step 5: spraying in an environment of 10°C to 25°C and relative humidity of 20% to 60%, adjusting the spraying pressure to 0.3MPa to 0.5MPa, the spraying distance to 150mm to 250mm, the single spraying to 10 to 25μm, the total spraying thickness to 150 to 200μm, and the surface drying time to 10min to 30min; Step 6: When the curing method is heat curing, the curing temperature is 60-120°C and the curing time is 2-10 hours. When the curing method is room temperature curing, the curing time is 24-72 hours, preferably 48-72 hours.
8. The method for preparing the spray-type white thermal control coating according to claim 7, characterized in that: The thickness of the thermal control coating is between 150 and 200 μm, the solar absorption ratio is 0.13 to 0.19, the hemispherical emissivity is 0.87 to 0.91, the adhesion is 0 to 1 level, and the substrate is aluminum alloy, magnesium alloy, magnesium-lithium alloy, titanium alloy, carbon fiber composite material or glass fiber composite material.
Citation Information
Patent Citations
A method for preparing magnesium-lithium alloy coatings from precursor polymers
CN102268678A
Room-temperature curing high-temperature-resistant organic silicon rubber coating as well as preparations method and application of room-temperature curing high-temperature-resistant organic silicon rubber coating
CN109593464A
High-temperature-resistant insulation coating and preparation method and application thereof
CN110373108A
Ultraviolet-irradiation-resistant low-absorptivity inorganic white thermal control coating and preparation method thereof
CN111393882A